(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Presently, tremendous usage of synthetic dyes would release massive amount of waste and unstable colourants sparkling serious health hazard and upsetting the ecosystem. Therefore, study needs to be directed to select a potential natural dye as Parkia speciosa to be applied on cotton textile. Colour fastness such as light fastness and wash fastness of dyed fabric were assessed. Study revealed that bleached fabric dyed with Parkia speciosa had good wash fastness and light fastness than the scoured fabric, dyed with Parkia speciosa.